2015
DOI: 10.1039/c5dt01370d
|View full text |Cite
|
Sign up to set email alerts
|

New thorium(iv)–arsonates with a [Th8O13]6+ octanuclear core

Abstract: Three new octanuclear Th(iv) arsonates, namely [Th(8)(O)(L)(6)(HL)(6)(H(2)O)(12)]·19.5H(2)O (1) (H(3)L = o-HO(3)S-C(6)H(4)-AsO(3)H(2)), [Th(8)(O)(L)(6)(HL)(6)(H(2)O)(10)]·17H(2)O (2) and [Th(8)(O)(L)(6)(HL)(6)(H(2)O)(5)]·0.5H(2)O (3), with o-sulfophenylarsonic acid as the bridging ligand, have been prepared under hydrothermal conditions. Each complex contains [Th(8)O(13)](6+) octanuclear cluster cores composed of two [Th(4)O(6)](4+) units bridged by a μ(2)-oxo anion. The structure of compound features a 0D hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This study confirms the trend of thorium to limit the condensation process and to generate relatively small inorganic clusters, whereas uranium or plutonium can lead to the production of giant polycondensed organization counting up to 38 metallic centers in molecular assemblies. , This limitation is explained well by a relative low Lewis acidity, compared to the other tetravalent actinides of this series.…”
Section: Discussionsupporting
confidence: 83%
“…This study confirms the trend of thorium to limit the condensation process and to generate relatively small inorganic clusters, whereas uranium or plutonium can lead to the production of giant polycondensed organization counting up to 38 metallic centers in molecular assemblies. , This limitation is explained well by a relative low Lewis acidity, compared to the other tetravalent actinides of this series.…”
Section: Discussionsupporting
confidence: 83%
“…Thermodynamic studies do not predict the Th 3 structural unit to exist in noncomplexing media over a pH range of 1–14 . Instead, only Th 4+ , [Th­(OH) x ] y+ , [Th 2 (OH) 2 ] 6+ , [Th 4 (OH) 8 ] 8+ , and [Th 6 (OH) 15 ] 9+ are proposed. , Monomers, dimers, tetramers, hexamers, octamers, and even a decamer are established in the solid-state for thorium. ,,,, , Thus, the isolation of 2 as a trimeric unit from aqueous solution illustrates the novelty of this complex. Of the previously reported trimers, Kadish et al established the persistence of the trimeric unit with a chelating porphyrin ligand in solution by NMR; Li and co-workers observed their Th MOF in aqueous solutions through hydrolytic stability measurements. , Other reports did not identify the trimer in solution.…”
Section: Discussionmentioning
confidence: 99%
“…It is the largest and least Lewis acidic of the tetravalent metal ions, yet exhibits fairly extensive hydrolysis and condensation chemistry, which has historically complicated interpretation of solution based studies and resulted in large discrepancies in thermodynamic literature . Over 1000 Th solid state structures have been reported in the Cambridge Structural Database and of those, approximately 50 arise from hydrolysis and condensation to include dimeric, trimeric, tetrameric, hexameric, octameric, , and decameric units, with the hexameric [Th 6 (OH) 4 O 4 ] 12+ species being the most prevalent. Yet the [Rn]­5f 0 electron configuration of Th has limited the number of spectroscopic handles available to assess the correlation between these solid state structural units and those present in solution, although it promotes ease when performing electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in inorganic synthesis and increased understanding of environmental colloids have provided new opportunities to explore the chemistry of actinides at the nanoscale. [44][45][46][47][48][49][50][51][52][53] Molecular cluster chemistry of the tetravalent actinides, exemplied by a class of actinide oxo hydroxide clusters, [54][55][56][57][58][59][60][61][62][63][64][65][66] has provided valuable structural insight into the growth of bulk AnO 2 (An ¼ actinide) by the controlled hydrolysis of molecular precursors. Synthetic techniques for actinide nanoparticles have also been reported that include direct decomposition of actinide precursors into nanoparticles in aqueous solutions by irradiation, 2,8,67 sonolysis 68,69 or via hydrothermal approaches.…”
Section: Introductionmentioning
confidence: 99%